Analisis Sistem Informasi Pengolahan Data Nilai Mahasiswa Menggunakan PIECES pada Prodi Sistem Informasi STTH-Medan - Nurjamiyah Nurjamiyah; Arie Rafika Dewi (Program Studi Sistem Informasi, 2018)
In some parts of the education system, there are teaching and learning activities involving students and lecturers. And when doing some teaching and learning activities, some progress of student learning occurred which are grades obtained from the student’s examination. Presently, the student’s grades are processed conventionally which is done by each lecturer manually using pen, paper and a calculator. Thus, the Department will have difficulties managing the student’s grades given by the lecturer and the results will not be optimal either. If done manually, the lecturer must calculate the grade for each student one at a time. Moreover, students will have to wait for a long time finding out for their grades. It will take a long time and requires high precision for accurate calculations if the student’s grades processed manually. A PIECES Analysis, which is analyzing performance, information, economics, applications, and services, is used in analyzing student information system of the Information System Department STTH-Medan. The purpose of this study is to find out the data processing system and the data needed for developing STTH-Medan Information System. By using PIECES Analysis, it will be done in detail, and can be used for information systems.Keywords: Analysis, Information Systems, Grades, PIECES, UML